Correction: The use of paracetamol during pregnancy: A qualitative study and possible strategies for a clinical trial. - Cathrine Vedel; Ditte Staub Jørgensen; David Møbjerg Kristensen; Olav Bjørn Petersen; Gorm Greisen (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0271537.].